A study on the spatial visual elements in extended reality content - Kim, Dong-Jo (Edelweiss Applied Science and Technology, 2025)
With the advancement of digital technology, spatial experiences are undergoing a significant transformation through extended reality (XR). This study investigates how spatial visual elements—including lighting, color transformation, texture, depth, and interactive viewpoints—contribute to user immersion in XR environments. Adopting a case study approach, the research examines The Sphere in Las Vegas, a state-of-the-art example of XR integration in architectural and performance design. Methodologically, this study evaluates The Sphere’s LED-paneled exterior and immersive interior environment, analyzing their impact on user perception and engagement. The findings indicate that real-time lighting adjustments, interactive three-dimensional (3D) elements, and dynamic scene transitions substantially enhance audience immersion, as exemplified by the Anyma performance. Furthermore, this research highlights the scalability of XR spatial visuals and their potential applications in diverse fields, including entertainment, education, architecture, and virtual collaboration. In conclusion, as XR technology converges with artificial intelligence (AI) and big data analytics, it is expected to become increasingly adaptive and personalized. This study underscores the necessity of optimizing XR content creation, interactive storytelling, and immersive spatial design strategies. From a practical perspective, industries incorporating XR can significantly enhance user experiences and redefine spatial interaction within both physical and virtual environments.